1999
DOI: 10.1002/(sici)1097-4547(19991015)58:2<207::aid-jnr1>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding CNS remyelination: Clues from developmental and regeneration biology

Abstract: A guiding principle in remyelination research has been to seek clues to its nature in developmental studies on myelination. This "recapitulation hypothesis" argues that the regenerative response involves rerunning much the same programme as occurs during the developmental process. Here we examine the extent to which current evidence supports this hypothesis and whether this is a useful conceptual framework within which to study remyelination and suggest that an equally fruitful approach is to look to regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 74 publications
3
50
0
2
Order By: Relevance
“…Franklin and Hinks (36) proposed that thin myelin sheaths in remyelination result from OLs unsheathing mature axons of mature diameter and length. In contrast in normal development, early myelin internodes adapt to changes in axon caliber and length by becoming thicker in diameter, and longer.…”
Section: Discussionmentioning
confidence: 99%
“…Franklin and Hinks (36) proposed that thin myelin sheaths in remyelination result from OLs unsheathing mature axons of mature diameter and length. In contrast in normal development, early myelin internodes adapt to changes in axon caliber and length by becoming thicker in diameter, and longer.…”
Section: Discussionmentioning
confidence: 99%
“…Activated astrocytes secrete the anti-inflammatory cytokine IL-10 (26), which inhibits the microglia antigen-presenting function, T cell proliferation, and cytokine synthesis by CD4 + T cells. TGF-β is expressed by all glial cells, including astrocytes in vivo and in vitro (36) and is implicated in the remyelination process (37). It deactivated microglia by down-regulating the expression of molecules associated with antigen presentation and production of proinflammatory cytokines, NO, and oxygen free radicals (38).…”
Section: Discussionmentioning
confidence: 99%
“…NT3, BDNF, and TGF-␤ are key regulators of oligodendrocyte survival and development (3,4). They are essential for the proliferation and recruitment of OPCs to the demyelinating lesions and for their subsequent differentiation into mature oligodendrocytes (19,20). It is therefore significant that in the present study, cell infiltrations were observed in the SCs of GA-treated mice and their location was not associated with damage, suggesting the involvement of GA-induced cells in the neuroprotective effect of GA on myelin.…”
Section: Discussionmentioning
confidence: 99%